Survey of Scientific Productions on the Use of Visual Resources in Mathematics Teaching to Deaf Students (Revista Educação, Artes e Inclusão, 2023)
Visual aids are mathematics teaching strategies that can be used in a classroom with deaf and listerner students. This research aimed to identify in the literature the use of visual resources in the teaching of mathematics for deaf students in high school and to compile the positive and negative strategies that document and guide the development of teaching materials for this audience in future works. For this task, this research adopted a qualitative approach following the methodology of systematic literature review in SciElo and BDTD journals. The results identified a difference between the works published in the deaf literature (n-4), compared to the listener (n-61). In general, the use of the blackboard, slides, writing on paper, illustrations, manipulable material, Graphequation software and video lessons were visual strategies documented as relevant in the Education of the Deaf in the area of ​​Mathematics. It is expected to contribute to the area, mapping the studies already produced and, with this, favoring future works focused on the production and testing of teaching materials
Keywords: visual resources; teaching of deaf; mathematics teaching